2006
DOI: 10.1093/cercor/bhl087
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for the GABAA Receptor-Mediated Tonic Inhibition in Rat Somatosensory Cortex

Abstract: Fast inhibitory synaptic transmission is primarily mediated by synaptically released gamma-aminobutyric acid (GABA) acting on postsynaptic GABA(A) receptors. GABA acting on GABA(A) receptors produces not only phasic but also tonic inhibitions by persistent activation of extrasynaptic receptors. However, the mechanistic characteristics of tonic inhibition in the neocortex are not well-understood. To address this, we studied pharmacologically isolated GABA(A) receptor-mediated currents in neocortical pyramidal n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 30 publications
2
73
0
1
Order By: Relevance
“…One salient difference between DGGCs and CA1 pyramidal cells is that tonic inhibition in CA1 pyramidal cells is mediated by ␣5 subunit-containing GABA A receptors, whereas ␦ subunit-containing receptors are dominant in DGGCs (Caraiscos et al, 2004;Glykys et al, 2008). In layer 2/3 pyramidal neurons there is little, if any, functional expression of ␦ subunits (although ␦ subunit mRNA is present) (Yamada et al, 2007). Thus, we speculate that signals produced by postsynaptic GABA B receptors may preferentially affect ␦ subunits.…”
Section: Mechanism Of Gaba B Receptor Modulation Of Gaba a Currentsmentioning
confidence: 84%
“…One salient difference between DGGCs and CA1 pyramidal cells is that tonic inhibition in CA1 pyramidal cells is mediated by ␣5 subunit-containing GABA A receptors, whereas ␦ subunit-containing receptors are dominant in DGGCs (Caraiscos et al, 2004;Glykys et al, 2008). In layer 2/3 pyramidal neurons there is little, if any, functional expression of ␦ subunits (although ␦ subunit mRNA is present) (Yamada et al, 2007). Thus, we speculate that signals produced by postsynaptic GABA B receptors may preferentially affect ␦ subunits.…”
Section: Mechanism Of Gaba B Receptor Modulation Of Gaba a Currentsmentioning
confidence: 84%
“…Because ␣5-subunit-containing GABA A receptors mediate tonic inhibition in other brain regions (Caraiscos et al, 2004;Scimemi et al, 2005;Yamada et al, 2007) and this subunit is expressed in the striatum (Pirker et al, 2000;Schwarzer et al, 2001), we studied the action of a selective inverse agonist of these receptors. Although micromolar concentrations of L655,708 have been used in the majority of brain slice physiology studies (Caraiscos et al, 2004;Scimemi et al, 2005;Yamada et al, 2007), pharmacological analysis of recombinant GABA A receptors (Quirk et al, 1996) would suggest that nanomolar concentrations should be as efficacious.…”
Section: Discussionmentioning
confidence: 99%
“…Although micromolar concentrations of L655,708 have been used in the majority of brain slice physiology studies (Caraiscos et al, 2004;Scimemi et al, 2005;Yamada et al, 2007), pharmacological analysis of recombinant GABA A receptors (Quirk et al, 1996) would suggest that nanomolar concentrations should be as efficacious. Indeed, we found that 50 nM L655,708 was as efficacious in antagonizing tonic currents in D 2 ϩ MSNs as the higher concentrations (10 M).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amplitude of tonic inhibition was analyzed as the difference between the holding currents measured before and after the application of the GABAA receptor antagonist bicuculline (10 μM) while the membrane potential was clamped at −75 mV. The holding current was calculated from 100 msec epochs containing no obvious spontaneous synaptic events, taken every four seconds during an 80-second period [24].…”
Section: Electrophysiological Recordingmentioning
confidence: 99%